Process Mining Techniques for Detecting Fraud in Banks: A Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Banks play an important role in a nation's economy, benefiting both residents and governments. In the recent past, many fraudulent happenings in banks have been identified as a result of vested interests. This paper examines the most common forms of insider fraud that occur in banks and attempts to categorise them. We include a description, factors associated to certain categories of fraud, and challenges in detecting frauds in this article. It is critical to identify such fraudulent events automatically until it is too late and get the individuals or groups of individuals into agreement. The process mining techniques is useful because it aids in the detection of irregular data.